Real-world Australian experience with tisagenlecleucel for relapsed/refractory diffuse large B-cell lymphoma—importance of pre-CAR-T optimization - Ho, Phoebe Joy; Vanguru, Vinay; Burge, Cale S.; Wayte, Rebecca; Brown, Christina; Bryant, Christian E.; Dunkley, Scott; McCulloch, Derek; Khoo, Liane; Favaloro, James; Jeffrey, Anthony; Solterbeck, Annie; et al. (Frontiers in Oncology, 2025)
IntroductionUp to 50% of patients with diffuse large B-cell lymphoma (DLBCL) relapse or are refractory to first-line therapy. Tisagenlecleucel, a CD19-directed chimeric antigen receptor (CAR)-T cell therapy, is approved for patients with relapsed/refractory (r/r) DLBCL in the third-line setting. Patients with r/r DLBCL treated with tisagenlecleucel in the real world have shown similar outcomes to those in clinical trials.MethodsWe report a single-center real-world analysis of patients with r/r DLBCL treated with tisagenlecleucel.ResultsAs of December 31, 2024, 63 patients with r/r DLBCL had received tisagenlecleucel (median follow-up, 15 months). Cytokine release syndrome occurred in 89%; 95% were grades 1/2. Immune effector cell-associated neurotoxicity syndrome was reported in 17% (10/11 cases mild; one case grade ≥3). The overall response rate was 79%, with 60% complete response (CR). The median duration of response was 26.4 months. The median progression-free survival (PFS) was 14.6 months, and the overall survival (OS) was 15.4 months. Patients whose response at day 30 was CR had a 42% reduction in risk of progression compared with those who achieved partial response (PR). High lactate dehydrogenase (LDH) at infusion was associated with a higher risk of disease progression (hazard ratio [HR] 2.1) and death (HR 2.65) than normal LDH, with the risk for progression increased 3.3-fold in a multivariate model. Almost one-third of our patients who achieved CR/PR had normalized their LDH at the time of infusion from a previously elevated level, of whom 87% (13/15) had received bridging therapy. Lack of response to bridging was associated with an almost twofold increased risk of progression compared with the responsive patients (3.1 vs. 19.5 months; HR 1.9; 95% CI: 0.9–3.9, P = 0.08).ConclusionWe demonstrated in this analysis that the safety and efficacy of tisagenlecleucel in patients with r/r DLBCL in an Australian real-world setting were better than in the pivotal JULIET clinical trial and other registry studies. We also confirmed the importance of achieving early CR and normalizing the LDH levels at CAR-T cell infusion to reduce the risk of disease progression. Our results suggest that bridging therapy played an important role in optimizing outcomes by managing pre-CAR-T disease control.